Penerapan Metode SMART Pada Sistem Pendukung Keputusan Rekrutmen Karyawan Baru - Humisar Hasugian; Agus Umar Hamdani; Wulandari Wulandari; Nofiyani Nofiyani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
At non-bank institutions, the recruitment process of new employees starts with the selection stage of the curriculum vitae, if they meet the requirements then process followed by psychological tests, interviews and programming tests. The determination of employees who are accepted to be hired by the companies is still subject to interviews results without considering other tests, therefor the hired employees are not ready for the work due to lack of technical ability. To overcome this problem, it is proposed to use a simple multi-attribute rating technique method for the processing of employee selection data because this method can process the data quantitatively and qualitatively with various assessments for each criteria and making the decision-making process easier and faster. The research objective is to assist the employee recruitment process using a web-based decision support system application by simple multi attribute rating technique method. The result of this study is in the form of a decision support system application website for recruiting new employees, using the criteria for Psycho-test Results (C1) weighting 20%, Age (C2) weighting 10%, Work Experience (C3) weighting 20%, Interview (C4) weighting 20%, and Mastery of Technical Aspects (C5) weighting of 30%. As for the alternative results of data processing using the above method are Febila Manda Dewi worth 0.666, Dini Apiani worth 0.447, Miqhiyal Noer Sopyani worth 0.890, and Irvan Egiawan worth 0.042, then based on the result it can be concluded that the prospective employee is Miqhiyal Noer Sopyani who got the highest score so he is recommended as the alternative new employee. The results of this study are objective due to the data processing is based on all criteria, so that the selected employees are certain to be ready to work.